Secretor Status Is Strongly Associated with Microbial Alterations Observed during Pregnancy. - Himanshu Kumar; Pirjo Wacklin; Massalin Nakphaichit; Eliisa Loyttyniemi; Somak Chowdhury; Yogesh Shouche; Jaana Mättö; Erika Isolauri; Seppo Salminen (PLoS ONE, 2015)
During pregnancy there are significant changes in gut microbiota composition and activity. The impact of secretor status as determined by genotyping FUT2 (fucosyltransferase 2) gene was taken as one of the confounding factors associated with faecal microbiota changes during pregnancy. In this prospective study, we followed women during pregnancy (total = 123 of which secretors = 108, non-secretors = 15) and characterised their gut microbiota by quantitative polymerase chain reaction (qPCR), Fluorescence In situ Hybridisation (FISH), Denaturing Gradient Gel Electrophoresis (DGGE) and pyrosequencing. qPCR revealed that C. coccoides group counts decreased significantly in non-secretors in comparison to secretors (p = 0.02). Similar tendency was found by FISH analysis in Clostridium histolyticum and Lactobacillus-Enterococcus groups between the secretor and the non-secretor pregnant women. DGGE analysis showed significant decrease in richness of Clostridium sp. between secretor and non-secretor mothers during pregnancy. Pyrosequencing based analysis at phyla level showed that there is greater increase in Actinobacteria in secretors in comparison to non-secretors, whereas Proteobacteria showed more increase in non-secretors. Change in relative abundance of Clostridiaceae family from first to third trimester were significantly associated with secretor status of pregnant women (p = 0.05). Polyphasic approach for microbiota analysis points out that the host secretor status (FUT2 genotype) affects the gut microbiota during pregnancy. This may lead to altered infant gut microbiota colonization.